Clinic and care: associations with adolescent antiretroviral therapy adherence in a prospective cohort in South Africa. (1st July 2021) - Cluver, Lucie; Shenderovich, Yulia; Toska, Elona; Rudgard, William E.; Zhou, Siyanai; Orkin, Mark; Haghighat, Roxanna; Chetty, Angelique N.; Kuo, Caroline; Armstrong, Alice; Sherr, Lorraine
Abstract : Objective: Adolescent antiretroviral treatment (ART) adherence remains critically low. We lack research testing protective factors across both clinic and care environments. Design: A prospective cohort of adolescents living with HIV (sample n  = 969, 55% girls, baseline mean age 13.6) in the Eastern Cape Province in South Africa were interviewed at baseline and 18-month follow-up (2014–2015, 2015–2016). We traced all adolescents ever initiated on treatment in 52 government health facilities (90% uptake, 93% 18-month retention, 1.2% mortality). Methods: Clinical records were collected; standardized questionnaires were administered by trained data collectors in adolescents' language of choice. Probit within-between regressions and average adjusted probability calculations were used to examine associations of caregiving and clinic factors with adherence, controlling for household structure, socioeconomic and HIV factors. Results: Past-week ART adherence was 66% (baseline), 65% (follow-up), validated against viral load in subsample. Within-individual changes in three factors were associated with improved adherence: no physical and emotional violence (12.1 percentage points increase in adjusted probability of adherence, P  < 0.001), improvement in perceived healthcare confidentiality (7.1 percentage points, P  < 0.04) and shorter travel time to the clinic (13.7 percentage points, P  < 0.02). In combination, improvement in violence prevention, travel time and confidentiality were associated with 81% probability of ART adherence, compared with 47% with a worsening in all three. Conclusion: Adolescents living with HIV need to be safe at home and feel safe from stigma in an accessible clinic. This will require active collaboration between health and child protection systems, and utilization of effective violence prevention interventions. Abstract : Supplemental Digital Content is available in the text